Impact of consolidation chemotherapy after delayed complete surgery in advanced epithelial ovarian cancer: a propensity score analysis. Issue 1 (14th December 2022) - Godfroy, Marine; Loaec, Cécile; Berton, Dominique; Guérin-Charbonnel, Catherine; Classe, Jean-Marc
Abstract : Objectives: This retrospective study aimed to assess the efficiency of consolidation chemotherapy after 6 cycles of neoadjuvant chemotherapy and delayed complete surgery on overall survival and progression-free survival among patients with advanced epithelial ovarian cancer. Methods: This was a retrospective consecutive study with a propensity score to ensure balance for the baseline characteristics between the study groups. All patients treated for advanced ovarian cancer with 6 cycles of neoadjuvant chemotherapy followed by delayed complete surgery, without post-operative chemotherapy (group 1), or with post-operative chemotherapy (group 2), were included. We evaluated survival and the quality of cytoreductive surgery using the propensity score. Results: From 2000 to 2017, 42 patients were included in group 1, and 59 in group 2. The median follow-up was 78 months (confidence interval (CI) 95% (60.1; not computable )). Neither progression-free survival nor overall survival were different between the two groups. The median progression-free survival was 10.2 months (CI 95% (8.8–17.0)) for group 1 and 10.4 months (CI 95% (7.9–12.8)) for group 2 (p=0.57). Five-year overall survival was 21.0% (CI 95% (10.4–42.3)) for group 1 and 26.1% (CI 95% (16.0–42.5)) for group 2 (p=0.73). Conclusions: Adding cycles of consolidation chemotherapy after delayed surgery following 6 cycles of neoadjuvant chemotherapy did not demonstrate any survival improvement in patients treated for advanced ovarian cancer not amenable to primary or interval surgery.